Identifikasi Senyawa Alkaloid dari Ekstrak Etanol Kulit Batang Strychnos ligustrina Menggunakan Liquid Chromatography-Mass Spectrometry (LC-MS) - Siti Wanda Nurwanti; Andriningrum Sarnoko; Atika Wulandari (Journal Borneo, 2023)
Bidara Laut (S. ligustrina) stem bark is commonly used by the society of West Nusa Tenggara and Bali as an antimalaria treatment. The study aims to quantify the number of chemical components from the alkaloid family present in the ethanolic extract of S. ligustrina bark. With a 70% ethanol-based solvent, the bark of S. ligustrina was extracted using the maceration process. LC-MS was used to assess the number of alkaloids present in the bark of S. ligustrina. In a reverse phase column using acetonitrile and formic acid as the mobile phases, gradient elution was carried out for 16 minutes. Five alkaloid compounds were discovered as a consequence of the investigation, including the 3-iso-ajmalicine molecule, which had an m/z of 353.1847 and a retention time of 4.26 minutes, and the brucine compound, which had an m/z of 395.1953 and a retention time of 5.06 minutes. The other 3 molecules are confirmed with m/z of that molecules C24H28N2O4, C22H24N2O3, and C11H17NO6 are 409.2107, 365.1848, and 260.1116, respectively, and their retention times are 4,90 minutes, 5,35 minutes, and 1,32 minutes. 3-iso-ajmalicine has just been confirmed to be present in S. ligustrina stem bark.